PRODUCTION OF CASTINGS WITHOUT PINHOLE POROSITY - A. N. Boldin; D. A. Soljakov (Литьë и металлургия)
The article is dedicated to pinhole porosity forming in castings at using of the slugs received under Cold-box-amin-process. The mechanism of pinhole porosity forming is revealed, new criteria of its prevention are established, recommendations on its prevention are given.